2017
DOI: 10.1371/journal.pone.0187040
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between public and private sectors of care and disparities in adverse neonatal outcomes following emergency intrapartum cesarean at term – A retrospective cohort study

Abstract: BackgroundPerinatal outcomes may be influenced by a variety of factors including maternal demographics and medical condition as well as socio-economic status. The evidence for disparities in health outcomes stratified by type of care (public or private) is lacking. The aim of this study was to investigate short term neonatal outcomes following category 1 and 2 emergency cesareans at term between publicly and privately funded women at a single major tertiary centre in Australia. Category 1—immediate threat to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…Neonates delivered at public health institutions had three times higher odds of neonatal mortality as compared to neonates who were delivered at private health institutions. This result was in line with the results of the study conducted in Australia ( 36 ). This might be because of the high coverage of birth in public health institutions as compared to private health institutions.…”
Section: Discussionsupporting
confidence: 92%
“…Neonates delivered at public health institutions had three times higher odds of neonatal mortality as compared to neonates who were delivered at private health institutions. This result was in line with the results of the study conducted in Australia ( 36 ). This might be because of the high coverage of birth in public health institutions as compared to private health institutions.…”
Section: Discussionsupporting
confidence: 92%
“…In an Australian single centre, retrospective, crosssectional study from 2007 to 2014 of 61,355 singleton term deliveries, neonatal outcomes following emergency CS were worse for women choosing public care rather than private care [19]. The differences in the public deliveries in low Apgar scores at 5 min, admissions to the Neonatal Critical Care and respiratory distress all persisted after multivariable analysis for feto-maternal factors.…”
Section: Discussionmentioning
confidence: 93%
“…Dahlen et al (2014) argued that it was clinicians' behavioural differences that increased private intervention rates, even among lowrisk women, which resulted in other adverse maternal and neonatal outcomes, and ultimately increased costs incurred. Conversely, other studies have found that neonatal outcomes were better in the private system (Robson et al, 2009;Adams et al, 2017Adams et al, , 2018Jang et al, 2017). In particular, Adams et al (2018) control for a vast number of risk factors and conclude that clinical practices may be partly responsible for lower neonatal mortality rates in the private system.…”
Section: Discussionmentioning
confidence: 87%
“…There are other models of care available in the public system which include the involvement of multidisciplinary obstetric teams if indicated by risk factors or complications (Adams et al, 2018). Public-private comparisons have shown that there are clear disparities in cost risk factors (William et al, 2018b) and clinical services (Roberts et al, 2000;Shorten & Shorten, 2000;Dahlen et al, 2012Dahlen et al, , 2014Einarsdóttir et al, 2012Einarsdóttir et al, , 2013bNippita et al, 2015) with mixed results on how this may impact on neonatal and maternal outcomes (Shorten & Shorten, 2002;Robson et al, 2009;Einarsdóttir et al, 2012Einarsdóttir et al, , 2013aDahlen et al, 2014;Adams et al, 2017Adams et al, , 2018Jang et al, 2017) by system; however, these studies have not investigated the detailed profiles of patients that enter into each system. Furthermore, there have been no studies that directly address the potential for adverse selection in private maternal health services, despite the substantially increased usage of private health insurance (PHI) during childbearing years for women (Australian Prudential Regulatory Authority, 2018).…”
Section: Introductionmentioning
confidence: 99%